Description of Mother's Knowledge About Diarrhea Prevention in Toddlers in Neighborhood Pillars 02 Community Pillars 03 Becirongengor Village - Ramadhan, Villa Putra; Moch. Bahrudin; Lestari, Citra (Global Ten Public Health and Nursing Journal, 2024)
Diarrhea is a state of defecation more than 3 times day accompanied by liquid stool in a 24-hour period (World Health Organization). The incidence of diarrhea in Indonesia is the number 2 cause of death in children under the age of 5 years. The knowledge possessed by a person, especially mothers, greatly influences the attitude of mothers in overcoming diarrhea in toddlers, because it is likely that diarrhea prevention measures at home by a mother are influenced by maternal knowledge, the better the mother's knowledge, the better the action against diarrhea prevention (Fani, 2020). So researchers are interested in examining the picture of maternal knowledge about diarrhea prevention in toddlers. This study aims to determine the picture of maternal knowledge about diarrhea prevention in toddlers in Neighborhood Association 02 Citizinens Association 03 Becirongengor Village. Analytical descriptive research design. The number of respondents was 40 mothers. This research will be conducted on January 16 – March 17, 2023. Assessment of the mother's picture of knowledge about the prevention of diarrhea in toddlers using questionnaires. Most mothers have sufficient knowledge of 30 people (75%), this shows that mothers have not been able to know about the prevention of diarrhea in toddlers properly and correctly. Due to the unclear receipt of information from competent health workers, it is difficult to receive information. The conclusion of this study is that the description of maternal knowledge about the prevention of diarrhea in toddlers in Neighborhood Association 02 Citizinens Association 03 Becirongengor village is mostly sufficient.